2009
DOI: 10.1179/174329008x286686
|View full text |Cite
|
Sign up to set email alerts
|

On role of stearic acid on morphology of Al–SiCpcomposite powders produced by mechanical alloying method

Abstract: In the present study high energy ball mill has been conducted to produce Al matrix composite reinforced with silicon carbide (SiC) at different milling time. To evaluate the role of stearic acid content on powder morphology of Al-SiC composite, the material has been fabricated with different stearic acid content, namely 0?1, 0?5, 1 wt-%. The SEM micrographs taken from Al-SiC composite powder show that the size of composite powders depends strictly on both stearic acid content and milling time. At constant mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…At present, silicon carbide nanoparticles (SiC NP ) have been implemented as a new reinforcements because of their good thermal and electrical conductivities, chemical stability, high mechanical strength, and low friction [3e8] , improving the tensile properties of many materials (i.e., aluminum-based alloys) at different temperatures when homogenously dispersed in metal-matrix [9e12] . Some related studies also show the unique ability of SiC NP to strengthen a metal matrix, while simultaneously maintaining good ductility [9,13] .…”
Section: Introductionmentioning
confidence: 97%
“…At present, silicon carbide nanoparticles (SiC NP ) have been implemented as a new reinforcements because of their good thermal and electrical conductivities, chemical stability, high mechanical strength, and low friction [3e8] , improving the tensile properties of many materials (i.e., aluminum-based alloys) at different temperatures when homogenously dispersed in metal-matrix [9e12] . Some related studies also show the unique ability of SiC NP to strengthen a metal matrix, while simultaneously maintaining good ductility [9,13] .…”
Section: Introductionmentioning
confidence: 97%
“…they found that SA preferentially adsorbed on the surface of alumina powder, which changed the flow behavior of the mixture, increasing the concentration of SA can reduce the uneven distribution of binder in injection molded parts, but it can also increase the possibility of bubble formation. Saberi et al 23 discussed a SA-assisted mechanical alloying method to prepare Al-SiC composite powders with different morphologies. They found that the addition of SA can reduce particle size and improve the uniformity of the composite powders.…”
Section: Introductionmentioning
confidence: 99%